WASATHIYAH ECONOMICS: RECONSTRUCTING A JUST ECONOMIC SYSTEM IN ISLAM - Elviyatur Rosyidah; Zahrotul Ilmiyah; Siska Syifa’ul Husna; Ali Mursyid Azisi (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2024)
This article examines the wasathiyah economic system that emphasizes aspects of benefit, justice and adheres to divine. This effort to reconstruct the discourse of wasathiyah economics aims to perfect the study of benefit-based economics in the portrait of moderation. The method used in writing this article is a descriptive analysis qualitative approach. Primary sources are taken from international and national accredited journals, books, and website articles that are credible and accountable. As a result, wasathiyah economy has at least four unique values including: divinely based, integrating science and morals, humanitarian insight, and moderate-based. While the basic principles that are firmly held in wasathiyah economics are the principle of divinity, bringing benefit, voluntariness, justice, and al-hurriyah (freedom) and al-mas'uliyah (responsibility). Another result of the analysis is that the advantages of wasathiyah economics are not the same as the capitalist and socialist economic systems, because these two economic principles do not involve the divine side in running the economy. In the end, this study can be useful theoretically for academics in exploring wasathiyah-based Islamic economic material. While practically it can be a guide for traders, entrepreneurs, economic drivers, government agencies and all people involved in the world of economics to stick to the principles of muamalah in accordance with religious guidance.